2011
DOI: 10.5254/1.3544676
|View full text |Cite
|
Sign up to set email alerts
|

Microdispersion of Silica in Tire Tread Compounds Above the Percolation Threshold by Tem Image Measurements

Abstract: Dispersion values in rubber are usually subjective values or the result of a comparison against empirical standards. we present a method to measure the filler dispersion in rubber compounds reinforced beyond the percolation threshold. Applying this method to an actual technical formulation with high filler loading, the dispersability of different silica grades, as well as the effect of coupling agent concentration in the dispersion has been showed. To carry out the measurements, the finished rubber is sliced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The minimum torque ( M L ) is related to the viscosity of composites, it is noticed that M L increased with increasing filler loading for all compositions of kaolin while for SBR/calcined kaolin composites M L increased up to 30 phr and then decreased. Also, M L for SBR/calcined kaolin seems to be greater than that of M L for SBR/kaolin, this increase is related to agglomeration between aggregates of kaolin occurred by means of direct contact through hydrogen bonding . The addition of smaller size filler particles tends to impose extra flow resistance due to higher molecular motion restriction of the macromolecules; hence higher viscosity can be detected .…”
Section: Resultsmentioning
confidence: 90%
“…The minimum torque ( M L ) is related to the viscosity of composites, it is noticed that M L increased with increasing filler loading for all compositions of kaolin while for SBR/calcined kaolin composites M L increased up to 30 phr and then decreased. Also, M L for SBR/calcined kaolin seems to be greater than that of M L for SBR/kaolin, this increase is related to agglomeration between aggregates of kaolin occurred by means of direct contact through hydrogen bonding . The addition of smaller size filler particles tends to impose extra flow resistance due to higher molecular motion restriction of the macromolecules; hence higher viscosity can be detected .…”
Section: Resultsmentioning
confidence: 90%
“…Transmission Electron Microscopy (TEM) was used by Julve et al [13] to evaluate the microdispersion of silica in a silica tire tread compound with a high filler content. Reuvekamp [14] found that a better silica microdispersion is obtained at high discharge temperature after mixing, as characterized by an increase in the amount of segregated silica particles.…”
Section: Introductionmentioning
confidence: 99%
“…It seems to be that for higher filler loadings, reliable and reproducible results cannot be obtained [108]. However, Julve et al [109] published a paper including a method to determine the dispersion quality of silica in a highly loaded vulcanized compound.…”
Section: Figure 230: Transformation Of the Three-dimensional Informamentioning
confidence: 99%